2014
DOI: 10.1080/13691058.2014.918282
|View full text |Cite
|
Sign up to set email alerts
|

Migration and HIV risk: life histories of Mexican-born men living with HIV in North Carolina

Abstract: Latino men in the Southeastern USA are disproportionately affected by HIV, but little is known about how the migration process influences HIV-related risk. In North Carolina (NC), a relatively new immigrant destination, Latino men are predominantly young and from Mexico. We conducted 31 iterative life history interviews with 15 Mexican-born men living with HIV. We used holistic content narrative analysis methods to examine HIV vulnerability in the context of migration and to identify important turning points. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The majority of migrant workers are Hispanic and work in rural areas in the United States (2). This overlooked community carries a heavy burden of working in an area that involves high occupational risk as well as a number of other challenges that come along with working in the fields of the US and obstacles associated with migration, and in many cases are also undocumented (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of migrant workers are Hispanic and work in rural areas in the United States (2). This overlooked community carries a heavy burden of working in an area that involves high occupational risk as well as a number of other challenges that come along with working in the fields of the US and obstacles associated with migration, and in many cases are also undocumented (14).…”
Section: Introductionmentioning
confidence: 99%
“…This overlooked community carries a heavy burden of working in an area that involves high occupational risk as well as a number of other challenges that come along with working in the fields of the US and obstacles associated with migration, and in many cases are also undocumented (14). These challenges include the neighborhood they reside in, long hours, employment instability; stigma associated with migrant status, language barriers, and social isolation and place these individuals at heightened vulnerability in engaging in unhealthy coping behaviors, which increase their risk of sexually transmitted infections (STIs), especially HIV/AIDS (2). In addition to these many challenges, migrant workers have also been significantly affected by HIV/AIDS (5).…”
Section: Introductionmentioning
confidence: 99%
“…Contextual factors, such as economic level, healthcare system efficiency, HIV prevalence, or legal status and social tolerance of homosexuality in the country of origin, and individual factors such as having multiple sexual partners, condomless sex, access to prevention, drug use, sex work, engagement with the gay scene, density of sexual network, may explain the increased risk of HIV exposure among migrant MSM [8,9]. Several studies carried out between 2010 and 2020 have shown that hardship during migration and in the first years after arrival in the host country influence emotional insecurity and risk taking with regards to HIV acquisition [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depression, anxiety and substance use have long been recognized as influential in the linkage and retention and overall quality of life of people living with HIV/AIDS (PLWHA), including Latinxs [ 6 8 ]. Foreign-born Latinx PLWHA often bear the added hardships of migration stress and trauma [ 9 , 10 ]. Mexican-born individuals living in the US are more likely to endure economic challenges, lack health insurance and immigration documentation, experience language and other barriers to care as well as inferior HIV-related outcomes [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%